Chronic respiratory diseases: A rapidly emerging public health menace - Prakash Prabhakarrao Doke (Wolters Kluwer Medknow Publications, 2023)
Chronic respiratory diseases, especially the common chronic obstructive pulmonary disease (COPD) and asthma, are increasing at a swift pace. Although smoking is the most typical risk factor globally, indoor and outdoor air pollution is more important in India. Deaths due to COPD have been next to coronary heart disease since 2014. It causes about 64 deaths per lakh population. It is a chronic and progressive disease having many exacerbations. Mostly senior males are affected. Often, the exacerbation needs intensive care, which may be taxing to the limited intensive care units and may deprive other more warranting patients. The diagnosis requires spirometry, which is available only in private or government tertiary care hospitals. The mainstay of treating both diseases is the inhalation of bronchodilators with or without steroids. The diagnosis and treatment are costly, and treatment is required lifelong. Reduction in risk factors is a challenging and long journey. It requires behavioral change communication. The government in the health sector has critical options. On the one hand, the disease is increasing for various reasons; on the other hand, resources are enormously required for prevention and management. The ASHA system and health and wellness centers, which have not been given due importance, can screen, diagnose, and manage majorly patients. Public health specialists should forcefully advocate for resources required for training and equipment.